Role of ST2 as a biomarker of respiratory dysfunction after interstitial pneumonia - Maria Civita Cedrone; Luca Marino; Marianna Suppa; Giuliano Bertazzoni (Open Journal of Asthma - Peertechz Publications, 2021)
Through stern social restraint measures, Italy has recently overcome the epidemic peak of COVID-19 (Coronavirus Disease-19) respiratory syndrome induced by SARS-CoV-2 and the attention is progressively moving toward its sequelae, especially on pulmonary fibrosis and the associated pulmonary functional decline [1-3].